2018
DOI: 10.3390/ma11091582
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Spark Plasma Sintering of ZrW2−xMoxO8 Exhibiting Controllable Negative Thermal Expansion

Abstract: Molybdenum-doped zirconium tungstate (ZrW2−xMoxO8) has been widely studied because of its large isotropic coefficient of negative thermal expansion (NTE). However, low density and poor sinterability limit its production and application. In this study, relative density greater than 90% single-phase ZrW2−xMoxO8 (0.0 ≤ x ≤ 1.0) sintered bodies were fabricated by spark plasma sintering (500–600 °C for 10 min) using ZrW2−xMoxO7(OH)2·2H2O precursor powders as the starting material. High-temperature X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The training data contains nearly 200 NTE materials from the published literature 16–127 and about 230 positive thermal expansion (PTE) data with the same structures or elements as NTE materials. To improve the reliability of the prediction capability, we employed the three-step ML method with data augmentation and cross-validation.…”
Section: Introductionmentioning
confidence: 99%
“…The training data contains nearly 200 NTE materials from the published literature 16–127 and about 230 positive thermal expansion (PTE) data with the same structures or elements as NTE materials. To improve the reliability of the prediction capability, we employed the three-step ML method with data augmentation and cross-validation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the investigation of alternative low-temperature liquid-phase methods is rather mandatory. It has been reported that ZrW 2 O 8 powders can be prepared by dehydrating its hydrate precursor ZrW 2 O 7 (OH) 2 •2H 2 O, which can be obtained using liquid-phase methods such as solgel [1,2,[29][30][31], hydrothermal [3,5,[32][33][34][35][36] and co-precipitation [35]. Kanamori et.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on SPS of ZrW 2 O 8 composites demonstrates the success of the method in achieving near-theoretical densities. [15][16][17] Wei et al 18 discussed how W can be partially substituted with Mo to overcome sinterability issues that arises due to the low-temperature phase transition in ZrW 2 O 8 . While these studies suggest solutions to address the discontinuity in the thermal expansion behavior of ZrW 2 O 8 , there are no prior reports on SPS of ZrMo 2 O 8 to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%